Spatial-temporal Changes and Driving Forces of Cultivated Land at County Level in Hu'nan Province from 2009 to 2018 - Chen Songlin; Zhao Xiang; Liu Zhongqiu; Pan Yupiao; Wang Xu (Shuitu baochi tongbao)
[Objective] The characteristics of spatial-temporal cultivated land change and its driving forces at county level in Hu'nan Province from 2009 to 2018 were analyzed in order to support the formulation of farmland protection policies. [Methods] The cultivated land dynamic index, landscape indices, and the Geodector model were used to determine the area, spatial distribution, and driving forces of cultivated land changes in Hu'nan Province based on land survey data. [Results] ① The total area of cultivated land increased by 379.02 km2 in Hu'nan Province from 2009 to 2018. The newly reclaimed cultivated land was mainly located in the area around Dongting Lake, the Central Hu'nan Basin group, and Northwest Hu'nan Province. ② Due to the implementation of land consolidation projects, the shapes of cultivated land patches became more and more regular over the past ten years. On the other hand, as the mean area of cultivated land patches became smaller and smaller, cultivated land patches in Hu'nan Province showed a significant trend towards fragmentation from 2009 to 2018 that was mainly due to urban-rural development and infrastructure construction. ③ The fiscal revenue and expenditure of local governments, population growth, the output value of agriculture were the main driving forces of cultivated land changes in Hu'nan Province from 2009 to 2018. These driving factors produced a comprehensive impact on the changes of cultivated land through interactions such as dual-factor enhancement and nonlinear enhancement. [Conclusion] The protection of cultivated land in Hu'nan Province has achieved remarkable results in the past 10 years. However, the protection of cultivated land in Hu'nan Province still faces some challenges. Therefore, cultivated land protection in Hu'nan Province during the next decade should give greater attention to the trade-offs between the development and protection of land resources. Development of new cultivated land should focus on reclamation of inefficient construction land in rural areas, rather than on occupying ecological space. Additionally, Hu'nan Province should also optimize policies for the protection and utilization of cultivated land that will promote the productivity of cultivated land so that market factors can play a stabilizing and sustaining role in cultivated land protection.